RESILIENSI ANAK PENDERITA THALASSEMIA DI ACEH - Barmawi; Syarifah Zainab; Maria Ulfa (Archetype : Jurnal Ilmiah Psikologi dan Terapan, 2025)
Thalassemia is a degenerative blood disorder that remains difficult to cure, with no definitive treatment currently available. Patients with thalassemia require lifelong blood transfusions, which often lead to various side effects. In social settings, children living with thalassemia experience significant lifestyle changes that set them apart from their peers, especially when they live in communities with little to no understanding of the illness. This study aims to explore the resilience levels of children with thalassemia in Aceh as they navigate daily life. A qualitative method with a phenomenological approach was employed, using interviews and observations for data collection. The findings indicate that resilience levels vary among individuals with thalassemia, influenced by differences in social support from parents, family, and the surrounding environment. The study highlights the need for community education about thalassemia to provide psychological support for patients and reduce the risk of bullying.